ПРОФЕСІЙНА РЕФЛЕКСІЯ ЯК УМОВА ФОРМУВАННЯ ІННОВАЦІЙНОЇ ДІЯЛЬНОСТІ МАЙБУТНЬОГО ПЕДАГОГА (Педагогіка вищої та середньої школи, 2007)
In the article is examined and is determined psychological -pedagogical aspect of forming of professional reflection in the conditions of innovative activity offuture teachers.